A decahaem cytochrome as an electron conduit in protein–enzyme redox processes. Issue 46 (19th May 2016) - Lee, Chong-Yong; Reuillard, Bertrand; Sokol, Katarzyna P.; Laftsoglou, Theodoros; Lockwood, Colin W. J.; Rowe, Sam F.; Hwang, Ee Taek; Fontecilla-Camps, Juan C.; Jeuken, Lars J. C.; Butt, Julea N.; Reisner, Erwin
Abstract : The decahaem cytochrome MtrC from Shewanella oneidensis MR-1 was employed as a protein diode between an indium tin oxide electrode and fumarate reductase or hydrogenase. Abstract : The decahaem cytochrome MtrC from Shewanella oneidensis MR-1 was employed as a protein electron conduit between a porous indium tin oxide electrode and redox enzymes. Using a hydrogenase and a fumarate reductase, MtrC was shown as a suitable and efficient diode to shuttle electrons to and from the electrode with the MtrC redox activity regulating the direction of the enzymatic reactions.